The synergy between Expanded Program on Immunization and Polio Eradication Initiative in Pakistan: a policy and program exploration - Zaeem Haq; Arshad K. Chandio; Shamsa Zafar; Faisal Iqbal; Ayesha Naeem; Saad Karim (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background Until recently, Pakistan had achieved significant milestones in polio eradication, and was close to becoming polio-free. The country has an Expanded Program on Immunization (EPI) since 1978 and a Polio Eradication Initiative (PEI) since 1994. PEI and EPI need to carry out synergized activities during the last leg of polio eradication; EPI taking over the responsibility for a polio-free Pakistan. Knowing the understanding and implementation of the synergy between the two programs is important at this critical juncture. # Methods We carried out a national-level exploration, comprised of 30 individual interviews and eight focus groups. The objectives were: (i) to explore the current understanding of the PEI-EPI synergy and its operationalization, especially for the zero-dose children at various levels, and (ii) to explore the context of the two programs, the synergy-related enablers and barriers, and suggestions to enhance synergy in the future. The participants included officials from various tiers along with health workers and vaccinators. # Results Four themes emerged. First, "synergy" has different meanings for different stakeholders; hence variable implementation models. Second, some synergies (e.g., sharing of surveillance data by PEI) are in place while additional (e.g., transferring human resources and enhancing community engagement) can be created. Third, the EPI and the PEI have become two unequal programs because of political factors, visibility, and funding. Fourth, the situation can be helped through clear policy and operational guidelines including roles and responsibilities. # Conclusions All stakeholders understand the importance of synergy. The willingness for the adoption of the interventions instituted by the PEI exists on both sides. The EPI, however, needs to enhance its capacity to absorb these interventions and improve service delivery. Given the context in which one partner has gained more political ownership, funding, and visibility than the other, the realization of the international donors, and the guidance from the Ministry of National Health Services, Regulations, and Coordination are essential for ensuring the polio legacy and achieving and maintaining the status of a polio-free Pakistan.